A Fuzzy Control Model for Restraint of Bullwhip Effect in Uncertain Closed-Loop Supply Chain With Hybrid Recycling Channels - Zhang, Songtao; Li, Xue; Zhang, Chunyang (IEEE transactions on fuzzy systems, 2017)
By considering the uncertainties in the closed-loop supply chain system with hybrid recycling channels, a fuzzy control model is constructed to restrain the bullwhip effect. Firstly, the basic models of the uncertain closed-loop supply chain with hybrid recycling channels are established where the manufacturer and the third party recovery provider collect the recycled products at the same time. Then, the basic models of the closed-loop supply chain are converted into a nonlinear fuzzy switching model based on the discrete Takagi-Sugeno (T-S) fuzzy control system. Secondly, a fuzzy robust control method is utilized to reduce the impacts caused by the internal and external uncertain factors on the closed-loop supply chain. This method can not only restrain the bullwhip effect, but also make supply chain remain robust stability. Finally, the simulation results show the feasibility and effectiveness of the constructed fuzzy control system.